2011
DOI: 10.1097/phh.0b013e3182140c47
|View full text |Cite
|
Sign up to set email alerts
|

Developing Leadership and Advocacy Skills in Medical Students Through Service Learning

Abstract: A curriculum in advocacy and leadership skills that includes an intensive, community-based service learning experience is effective at increasing student empowerment and disposition toward community service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 5 publications
3
77
0
Order By: Relevance
“…As in other reports in the literature, (Long et al, 2011;Meili et al, 2011;Liang En et al, 2011;Chastony et al, 2013) our students reported that the community component was a stimulating, enjoyable and positive experience. It provided them with skills and knowledge of the local community and population that could not be gained from formal lectures.…”
Section: Discussionsupporting
confidence: 67%
“…As in other reports in the literature, (Long et al, 2011;Meili et al, 2011;Liang En et al, 2011;Chastony et al, 2013) our students reported that the community component was a stimulating, enjoyable and positive experience. It provided them with skills and knowledge of the local community and population that could not be gained from formal lectures.…”
Section: Discussionsupporting
confidence: 67%
“…For example Groh et al (2011) found that nursing students (n = 306) had a significant positive change in self-rated leadership skills following a SL experience, while Long et al (2011) reported no change in medical students' perceived effectiveness, willingness or understanding of leadership skills despite a greater appreciation of leadership roles.…”
Section: )mentioning
confidence: 99%
“…SL projects are designed, implemented and evaluated collaboratively with the intent of applying students' theory to practice while simultaneously targeting community identified needs. A number of studies (Burrows et al, 1999;Peterson & Schaffer, 1999;Beling, 2003;Bentley & Ellison, 2005;Goldberg et al, 2006;Johnson, 2007;Neill et al, 2007;Casey & Murphy, 2008;Kearney, 2008;Dauenhauer et al, 2010;Liang En et al, 2011b;Long et al, 2011;Pakulski, 2011;Reading & Padgett, 2011;Vogt et al, 2011;Zucchero, 2011) found that students gained a deeper understanding and application of knowledge through SL projects and experiences.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations